Implementation Of Cooperative Learning Model Type Of Thinking Aloud Pairs Problem Solving (TAPPS) Evaluating From Students' Confidence Attitude At SMP N 2 Baki - Yanuarti, Maghfiroh; Mahendrawan, Ersam; Prasetyo, Hendri (CV. Inara, 2022)
The objectives of this study aim to test and analyze (1) differences in the effect of learning models on students' mathematics learning achievement; (2) differences in the effect of students' self-confidence on students' mathematics learning achievement; and (3) the interaction between learning models and students' self-confidence towards students' mathematics learning achievement. In this study, the writer used quantitative research with a quasi-experimental design. The population and sample in this study were class VIII students of SMP N 2 Baki, and the sampling technique used was cluster random sampling. Data collection techniques used include questionnaires, tes, and documentation. The techniques of data analysis employ a two-way analysis of variance with cells not equal with α = 5% to obtain the results: (1) There is no difference in the effect of the learning model on students' mathematics learning achievement; (2) There are differences in the effect of students' self-confidence on students' mathematics learning achievement; and (3) There is no interaction between the learning model and students' self-confidence towards students' mathematics learning achievement.